The folds on a surface of equilibriumcondensation temperatures, referring to a vapor phase, for two-phase multicomponent mixtures. - D. I. Bushina; L. A. Serafimov; V. N. Stepanov (Тонкие химические технологии)
The regularities, defining course of lines of the relative extremums of condensationtemperature and α=1 lines, referring to a vapor phase, provided that the ideal vapor phase is equilibrium to a non-ideal fluid phase, on the basis of the equation of correlation of the equilibrium-condensation temperature scalar field and the vapor-liquid tie-line vector field for multicomponent two-phase mixtures, are reviewed.